Assessment of the coronal plane trunk symmetry in children. (1st December 2020) - Matlęga, Anna; Stępowska, Jolanta; Wiśniewski, Andrzej; Gajewski, Jan
ABSTRACT: Objective : To present the use of Posterior Trunk Symmetry Index (POTSI) and Anterior Trunk Symmetry Index (ATSI) for the assessment of the coronal plane trunk symmetry in children; to compare the two measures in individual subjects and to evaluate the possible association of each measure with gender and age (<6 vs. >6 years). Methods : Trunk photographs in uncorrected standing position were taken and analyzed to calculate POTSI and ATSI from measurements in 50 healthy children (64% girls), mean age 7.1 ± 3.38 years. The raw data were normalized. Results : Mean POTSI: 28.45 ± 13.28 (normal values <27); mean ATSI: 35.54 ± 20.81 (normal range not established). No correlation was found between the POTSI and ATSI ( r = 0.179; p = 0.21). There were no differences in the POTSI and ATSI between genders and age groups (<6 vs. >6 years). Trunk symmetry in coronal plane may be assessed with POTSI and ATSI parameters in children as young as approximately 2 years old if they cooperate. Conclusion : In healthy children, the values of POTSI and ATSI were independent of gender and chronological age. The combined use of POTSI and ATSI measurements in the same child seems a valuable tool for comprehensive trunk symmetry assessment but its application to physiotherapy practice requires further studies.